2021
DOI: 10.1016/j.outlook.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate nursing students’ perceptions on nursing education during the 2020 COVID-19 pandemic: A national sample

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 26 publications
6
109
0
18
Order By: Relevance
“…At the same time that schools of nursing shifted from brick and mortar to remote instruction, hospitals across the United States canceled in-person clinical experiences. Both quantitative and qualitative studies have described U.S. nursing student experiences during this abrupt transition as traumatic, stressful, and filled with fear, uncertainty, loneliness, and missed opportunity ( Diaz et al, 2021 ; Fitzgerald & Konrad, 2021 ; Goddard et al, 2021 ; Kim et al, 2021 ; Michel et al, 2021 ). The presence of depressive symptoms in nursing students was well-documented before the COVID-19 pandemic ( McDermott et al, 2020 ; Tung et al, 2018 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…At the same time that schools of nursing shifted from brick and mortar to remote instruction, hospitals across the United States canceled in-person clinical experiences. Both quantitative and qualitative studies have described U.S. nursing student experiences during this abrupt transition as traumatic, stressful, and filled with fear, uncertainty, loneliness, and missed opportunity ( Diaz et al, 2021 ; Fitzgerald & Konrad, 2021 ; Goddard et al, 2021 ; Kim et al, 2021 ; Michel et al, 2021 ). The presence of depressive symptoms in nursing students was well-documented before the COVID-19 pandemic ( McDermott et al, 2020 ; Tung et al, 2018 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Nursing education is unique in that it is primarily offered in-person, with a reliance on hands-on learning ( Michel et al, 2021 ; Wallace et al, 2021 ). When the COVID-19 pandemic began in Spring 2020, nursing programs had to rapidly shift from in-person to remote learning due to infection fears and limited personal protective equipment (PPE).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are few published studies on the impact of these changes in nursing education within the US ( Michel et al, 2021 ). A study conducted in December 2020 with undergraduate nursing students from five schools in the US found that students reported high levels of stress (due to school and personal reasons), difficulty learning online, and missed opportunities for hands-on clinical learning ( Michel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Öğrenciler alıştıkları kalabalık sınıf ortamından bir anda uzaklaşıp teknolojik cihazlara uyum sağlamaya çalışmışlardır. Bu süreçte her öğrencinin adaptasyon süresi aynı olmamıştır 15 . İnternet, bilgisayar ve telefon gibi teknolojik imkânlar açısından sınırlı olan öğrencilerde derslere düzenli katılım sağlanamamıştır.…”
Section: Discussionunclassified